2021
DOI: 10.13057/biodiv/d221060
|View full text |Cite
|
Sign up to set email alerts
|

Genetic control of fruit shelf life and yield in crossbreeding of Sletr1-2 mutant with Indonesian tropical tomatoes

Abstract: Postharvest losses are a significant concern for tomato breeding associated with their short fruit shelf life. Sletr1-2 is a new ethylene receptor mutant that has a prominent character in a prolonged fruit shelf life. This research aimed to estimate the combining ability of Sletr1-2 mutant and determine the selection method for future breeding associated with the fruit shelf-life and yield. Four lines of tropical tomato, i.e., 'Intan,' 'Mirah,' 'Ratna' and 'Mutiara,' were crossed with the wild type Micro-Tom (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…These mutants can be used as elders in plant breeding programs to produce new superior tomato cultivars with longer fruit shelf life (Mubarok et al, 2015;Wiguna et al, 2021). With the production of this shelf-resistant commercial tomato cultivar, the post-harvest problem in tomato fruits can be solved.…”
Section: Future Perspectivementioning
confidence: 99%
“…These mutants can be used as elders in plant breeding programs to produce new superior tomato cultivars with longer fruit shelf life (Mubarok et al, 2015;Wiguna et al, 2021). With the production of this shelf-resistant commercial tomato cultivar, the post-harvest problem in tomato fruits can be solved.…”
Section: Future Perspectivementioning
confidence: 99%
“…The fruit shelflife could be changed by altering cell wall deposition rather than cell wall hydrolytic enzymes. Genetically, according to Wiguna et al (2021) the fruit shelfcontrol bye additive gene action.…”
Section: Quantitative Charactersmentioning
confidence: 99%
“…An approach to this issue is developing tomato cultivars with an extended shelf life. Previous research has shown that genetic mutations that affect specific genes can alter fruit ripening, senescence, and shelf life [4] [5]. Hybridization is a promising strategy for developing new tomato varieties with desirable traits, as it involves crossing two genetically different individuals.…”
Section: Introductionmentioning
confidence: 99%